Screening of Native and Exotic Tree Species in Chile for Element Absorption from Dairy Slurry - Quiroz-Espinoza, M (Springer, 2019)
We studied the effect of fertigation with cattle slurry on native and exotic arboreal tree species in Chile. The objectives were to identify the most promising species for buffer strips to mitigate the stream pollution in dairy facilities, to determine where most nutrients accumulate (leaves, stems, or roots), and to test whether the native species are or are not a better biofilter than the exotic ones. We hypothesized that the individuals that were fertilized would have a higher nutrient concentration, nutrient accumulation, and growth than those non-fertilized. N and K concentrations were similar in fertilized trees and in the controls, while the P, Ca, Mg, and Na concentrations were higher in the control than those in the fertilized trees. Most species responded positively to fertilization on a dry matter basis. Luma apiculata, Drimys winteri, and Blepharocalyx cruckshanksii responded to fertilization showing a greater height and diameter growth. Generally, nutrients accumulated in leaves. Overall, the exotic Eucalyptus nitens was the species that accumulated more nutrients given its large growth rate. The native species that more commonly stood out in this study were D. winteri, Nothofagus dombeyi, and L. apiculata. In general, a minor proportion of the applied slurry was absorbed by trees, and we recommend the use of trees in biofilters as a complement to crop and pasture absorption. © 2019, Sociedad Chilena de la Ciencia del Suelo.